Implementasi Shariah Compliance Pada Produk Gadai Emas di Pegadaian Syariah dan Bank Syariah Mandiri - Nova Purnama Sari (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2020)
Shariah compliance in “rahn emas” business sharia in the current era tends to be often violated by Islamic companies in order to obtain greatest profits. Eventhough, interest in “rahn emas” business sharia is increasing. On the other hand, the component of sharia compliance is the main differentiator between Islamic companies and conventional companies. Therefore, this study aims to analyze how the implementation of sharia compliance in “rahn emas” products applied to the Pegadaian Sharia and Mandiri Sharia Bank in Metro City, Lampung. The study was conducted in 2019 at Pegadaian Sharia and Mandiri Sharia Bank in Metro City. The research method used is a case study in both Islamic companies, with a qualitative descriptive analysis method by comparing the implementation of “rahn emas” in both Islamic companies with the MUI fatwa and six indicators of sharia compliance. The results showed that Pegadaian Sharia and Mandiri Sharia Bank in Metro city generally conducted “rahn emas” operational activities based on the MUI DSN fatwa and sharia compliance indicators. However, in practice there is one point that contradicts the DSN MUI fatwa, which is to set maintenance costs following the loan amount. This is contrary to the MUI fatwa No. 26 of 2002 that is the costs and costs of storing goods (marhun) are borne by the pawners (rahin). Therefore, Pegadaian Sharia and Mandiri Sharia Bank in Metro City are expected to be able to make improvements and find a formula for determining administrative costs and maintenance costs in accordance with the DSN MUI fatwa.